TESTING AND ANALYZING OF IMPACT SIGNAL PERIODICITY IN ROLLING BEARING - SUDRAJAT (NIM : 13103040); Pembimbing Dr. Ir. Zainal Abidin, JAJAT
Bearings have significant role in industry because all rotating components are supported by bearings. Any defect on bearing can cause vibration which may initiate failure of a machine. Therefore, a good understanding of their vibration characteristics is an important information. On bearing with defect, the impact signal always appeared in the vibration measurement but it is not certainly periodic. This signal has unique characteristics which depend on its location. In this research, the characteristics of impact signal periodicity will be studied. The result of this research showed that the impact signal appeared periodically with unique characteristics. In this research, the highest periodicity occured on the bearing with the outer race defect. In such condition, the curve of its impact signal periodicity was a decline linear line, whereas the curve of impact signal periodicity due to the inner race defect on bearing was a sinusoidal curve.